2017
DOI: 10.1111/1759-7714.12429
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and computed tomography findings in Chinese lung cancer patients with HIV infection: A multi‐center study

Abstract: BackgroundThe study was conducted to investigate clinical and computed tomography (CT) features in Chinese lung cancer patients with human immunodeficiency virus (HIV).MethodsForty consecutive lung cancer patients with HIV were included. Clinical data were collected, and CT features were reviewed and measured. The factors associated with stages of cancer and the CT features with opportunistic pulmonary infections (OPIs) were also analyzed.ResultsThirty‐four of the patients were men (85%), and the mean age was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…Non-HIV specific risk factors for cancer are well described and include obesity as well as coinfections, that is oncogenic viruses such as human papilloma virus (HPV) and viral hepatitis [29], while chronic inflammation may also play a role [30,31]. Taken together, these findings could suggest that the association between smoking and cancer varies based on HIVrelated immune impairment and inflammation, which potentially increases the carcinogenic effects of smoking on PLWH [22,[32][33][34][35]. To date, there is no evidence to support this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Non-HIV specific risk factors for cancer are well described and include obesity as well as coinfections, that is oncogenic viruses such as human papilloma virus (HPV) and viral hepatitis [29], while chronic inflammation may also play a role [30,31]. Taken together, these findings could suggest that the association between smoking and cancer varies based on HIVrelated immune impairment and inflammation, which potentially increases the carcinogenic effects of smoking on PLWH [22,[32][33][34][35]. To date, there is no evidence to support this hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of HAART was not proven to be an independent risk factor for NADCs . HAART exposure did not play any role in lung cancer staging . No association was shown between HAART use and the risk of lung cancer .…”
Section: Hiv and Cancer Treatment In The Haart Eramentioning
confidence: 84%
“…19 HAART exposure did not play any role in lung cancer staging. 106 No association was shown between HAART use and the risk of lung cancer. 107,108 The opposite trend is observed in prostate cancer, where the cumulative antiretroviral exposure decreases cancer risk, though no difference was observed between people with or without antiretroviral therapy.…”
Section: Haart and Cancer Preventionmentioning
confidence: 99%
“…A similar study conducted on Chinese cohorts by Cheng et al . suggested that the majority (85%) of the HIV patients with lung cancer had non-small cell carcinoma and that nearly half of the study groups were at stage IIIb and IV of lung cancer 36 .…”
Section: Lung Cancermentioning
confidence: 99%